Slider posture effects on air bearing in a heat-assisted magnetic recording system - Myo, Kyaw Sett (2013)
This paper reports the effects of slider posture on the slider bearing in a heat-assisted magnetic recording (HAMR) system with the direct simulation Monte Carlo (DSMC) method. In this HAMR system, the heat issues on the slider bearings are assumed to be caused by a heated spot on the disk and/or slider body itself at various pitch angles. The simulation results show that with a heated spot on the disk, the air bearing pressure and air bearing force that acted on the slider surface will increase when the pitch angle becomes larger. It is also found that the bearing force increases with the heated spot size and the effects of a heated spot become more obvious at a larger pitch angle. On the other hand, the slider body temperature is observed to have a noticeable effect on air bearing pressure and force. The smaller pitch angle enlarges the tendency of bearing force variations with the slider temperature and makes the slider more sensitive to its temperature changes.